A systematic review of the use of magnetic resonance imaging in non-conditional pacemakers and implantable defibrillators. (14th October 2021) - Murphy, R; Kerley, R K; Kearney, P K
Abstract: Background: Cardiac implantable electronic devices (CIEDs) were long considered a contraindication for magnetic resonance imaging (MRI). Modern devices are now MRI conditional, but still the majority of CIEDs in the population are legacy devices and are classified as unsafe for MRI. There is growing consensus that MRI is also safe in these patients. Purpose: The purpose of this study was to perform an up to date systematic review of the evidence evaluating the use of MRI in patients with non-conditional CIEDs. Methods: Searches of the PubMed, CINAHL and Embase databases were performed. Studies that assessed the rate of adverse outcomes after MRI in patients with non-conditional CIEDs were included. Studies were excluded if they did not disclose the conditionality of patients CIEDs. Case reports or case series were not included. Results: 36 cohort studies were identified. No patient in these studies died during or immediately after MRI. Symptom associated with either torque or heating occurred in <1% of patients. Electrical resets occurred 1–2% of patients. There were no cases of non-conditional lead or generator failure. Inappropriate pacing occurred in <1% of patients. No ICD shocks occurred during MRI. Changes in CIED parameters occurred in 1–4% of patients. Conclusions: This systematic review highlights the relative safety of the use of MRI in patients with non-conditional CIEDs. Demonstrated be the fact that no deaths or device shocks have been suffered as a consequence of MRI in any of these studies, and the extremely low incidence of device or lead related complications. Still strict selection and monitoring protocol should be used when imaging these patients. Funding Acknowledgement: Type of funding sources: None.